Room temperature annealing of SnS2 films with electron impulse force. (February 2023) - Al-Mamun, Nahid Sultan; Wolfe, Douglas E.; Haque, Aman; Yim, Jae-Gyun; Kim, Seong Keun
Abstract: Tin disulfide (SnS2 ) is a layered metal dichalcogenide material with wide bandgap favoring electronics, sensors, photovoltaics, and water splitting applications. Atomic layer deposition can precisely control film thickness over large area, which is important for device applications. The as-deposited SnS2 shows poor crystallinity, which is difficult to anneal with high temperature because of de-sulfurization. We demonstrate room temperature annealing by exploiting electron impulse force. High current density pulses were applied with very low duty cycle to suppress heat accumulation, while the momentum of the electron pulses interacted with the defects and grain boundaries. For seven-layer thick tin di-sulfide specimens, resistivity was decreased by ten times at ambient temperature. Enhancement of crystallinity was analyzed with Raman spectroscopy and transmission electron microscopy followed by geometric phase analysis. The demonstrated technique can impact applications where post-synthesis annealing requires high temperature and special environment. Graphical abstract: Image, graphical abstract